Hypertext versus Footnotes: High School English Learners’ Online Reading Recall - Ebsworth, Miriam Eisenstein; McDonell, Tommy; DeFazio, Anthony; Cai, Chencen (IALLT Journal of Language Learning Technologies, 2017)
This study considers forty adolescent English Language Learners who read a passage online containing additional information available through either hypertext links or footnotes. Participants were attending a special high school for English learners at the time of the study. Two versions of the text were offered, one with hypertext and the other with footnotes, and participants were randomly assigned to the footnote or hypertext condition. Answers to multiple choice questions showed no significant difference between groups in recall of the reading under the two conditions, in contrast with an earlier study of learners in higher education settings whose recall of reading with hypertext was significantly lower than with footnotes. Learners’ ratings of perceived comprehensibility of the 2 texts was also not significantly different. Additional interpretive data came from focus group interviews involving all of the participants.